Internet of Things Infrastructure Research Mapping - Loso Judijanto (Westscience Press, 2026)
The fast pace of developing the concept of digital transformation made the Internet of Things infrastructure a crucial basis for connected systems, intelligent applications, and sustainable technological ecosystems. The purpose of this study is to conduct a bibliometric analysis and identify the patterns of development, intellectual structure, collaboration, and current research trends in the IoT infrastructure. Scientific publications related to the topic were gathered and analyzed using the software VOSviewer in order to investigate citation performance, co-authorship network, collaborations between institutions and countries, co-occurrence of keywords, thematic dynamics, and patterns of research density. It was found out that there has been a considerable increase in the amount of IoT infrastructure research, with cybersecurity, secure communication, edge computing, fog computing, smart cities, and intelligent infrastructure being identified as leading research topics. Citation analysis suggests that papers dedicated to IoT security framework, intrusion detection system, critical infrastructure protection, and distributed computing architecture have had a significant impact on this field. Collaboration analysis has indicated the presence of strong international research networks with China, India, USA, Germany, and the UK being recognized as the key contributors. Finally, it has been found out that the research has evolved from addressing connectivity challenges to advanced research which includes artificial intelligence, machine learning, privacy protection, energy efficiency, and autonomous IoT systems.